Development of mucus-penetrating antibiotic and quorum sensing inhibitor nanoparticle complex for bronchiectasis therapy - Tran, The Thien (Nanyang Technological University, 2020)
Bronchiectasis is a chronic respiratory disease characterized by permanent and irreversible dilatation of the airways caused by a vicious cycle of infection and inflammation, leading to the loss of lung function, morbidity, and mortality. Early results suggested inhaled ciprofloxacin (CIP) as a promising therapeutic avenue for bronchiectasis. Herein our study aims i) to investigate the effectiveness of the dry powder inhaler (DPI) formulation of CIP nanoplex in the mucus environment of bronchiectasis evaluated against its native CIP counterpart, ii) to further evaluate the effectiveness of the DPI of CIP nanoplex in comparison with the DPI of CIP liposome, iii) to improve the mucus permeability of the CIP nanoplex by equipping it with the mucolytic papain (PAP) protease hydrolyzing the mucin matrix in sputum, and iv) to enhance the antimicrobial efficacy against Pseudomonas aeruginosa biofilm by developing the nanoplex of quercetin – an effective quorum-sensing inhibitor of P. aeruginosa. The effectiveness of the DPI of CIP nanoplex was first evaluated in terms of (1) dissolution characteristics in artificial bronchiectasis sputum medium, (2) ex vivo mucus permeability in sputum from non-cystic fibrosis bronchiectasis (NCFB) and healthy individuals, (3) antibacterial efficacy in the presence of sputum against clinical P. aeruginosa strains (planktonic and biofilm), and (4) cytotoxicity towards human lung epithelial cells and so on. In our first evaluation, the DPI of CIP nanoplex exhibited superior mucus penetration and antibacterial efficacy to its native CIP counterpart. In the second evaluation, the DPI of CIP nanoplex was compared to the DPI of CIP liposome in the presence of NCFB sputum environment. Both the CIP nanoplex and CIP liposome exhibited similar bactericidal activities against planktonic and biofilm P. aeruginosa even though the DPI of CIP liposome exhibited slightly superior mucus permeability to the DPI of CIP nanoplex. However, it was found that the CIP liposome possessed much lower CIP payload than the nanoplex (3.5% versus 84%), resulting in high lipid contents in its DPI formulation that led to higher cytotoxicity and lower aerosolization efficiency, indicating that the CIP nanoplex can be a highly promising CIP delivery therapy for NCFB owed to its simpler preparation, higher CIP payload hence lower dosage, better aerosolization, and lower cytotoxicity. To further improve the mucus permeability hence the antibacterial efficacy, the CIP nanoplex was incorporated with a mucolytic enzyme papain (PAP) at the nanoplex formation step to produce the CIP-(DXT-PAP) nanoplex exhibiting built-in mucolytic capability. It was found that the CIP–(DXT–PAP) nanoplex exhibited ten-fold improvement in the mucus permeability compared to its CIP–DXT nanoplex counterpart, resulting in the former’s superior bactericidal activity against clinical P. aeruginosa biofilm in the presence of mucus barrier. Nevertheless, the incorporation of PAP above a certain concentration threshold caused cytotoxicity towards human lung epithelium cells. Therefore, the optimal dosing of the CIP–(DXT–PAP) nanoplex must be carefully determined. In the end, to further enhance the antibacterial efficacy and prevent the antibiotic resistant P. aeruginosa biofilm in the lung of bronchiectasis patients, the quercetin (QUE), a water-poorly soluble but effective quorum-sensing inhibitor against P. aeruginosa biofilm, was developed into the amorphous QUE nanoplex. It was found that the QUE nanoplex exhibited superior inhibition of P. aeruginosa biofilm and quorum sensing to the control, indicating that the QUE nanoplex can be a promising nanoparticle formulation strategy for bronchiectasis therapy.